1986
DOI: 10.1113/expphysiol.1986.sp002962
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGICAL ABNORMALITIES IN MYELINATED NERVE FIBRES CAUSED BY LEIURUS, CENTRUROIDES AND PHONEUTRIA VENOMS AND THEIR PREVENTION BY TETRODOTOXIN

Abstract: SUMMARYMorphological changes in peripheral nerve caused by the venoms of the scorpions Leiurus quinquestriatus and Centruroides sculpturatus were compared with those caused by Phoneutria nigriventer spider venom. Both scorpion venoms are known to delay the inactivation of sodium currents, Centruroides venom also altering the voltage dependence of sodium gating. Venom was injected by means of a glass micropipette into the sciatic nerves of anaesthetized mice. After survival times ranging from 15 min to 24 h the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Previous studies using nerve excitability measures in ESKD demonstrated a pattern consistent with axonal membrane depolarization, with changes correlating strongly with potassium concentration . Membrane depolarization due to chronic hyperkalaemia may result in nerve enlargement secondary to swelling of the node of Ranvier and myelin sheath as well as expansion of the periaxonal space . Of note, the present study demonstrated significant correlation between INBF and nerve excitability values, suggesting a close interaction between electrolyte imbalance, impaired nerve function and altered nerve morphology and blood flow.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies using nerve excitability measures in ESKD demonstrated a pattern consistent with axonal membrane depolarization, with changes correlating strongly with potassium concentration . Membrane depolarization due to chronic hyperkalaemia may result in nerve enlargement secondary to swelling of the node of Ranvier and myelin sheath as well as expansion of the periaxonal space . Of note, the present study demonstrated significant correlation between INBF and nerve excitability values, suggesting a close interaction between electrolyte imbalance, impaired nerve function and altered nerve morphology and blood flow.…”
Section: Discussionsupporting
confidence: 76%
“…These effects were attributed to activation of voltage-dependent sodium channels in both nerve and muscle fibres (Fontana & Vital-Brasil, 1985). Morphological changes produced by the venom in peripheral nerves of mice were also reported (Cruz-Hofling et al, 1985;Love et al, 1986).…”
Section: Introductionmentioning
confidence: 81%
“…Progressive neurodegeneration may spontaneously resolve the neuropathic pain, but decreased response thresholds (Lennertz et al, 2011) and loss of epidermal innervation of C fibers in the feet (Beiswenger et al, 2008) can contribute to negative neuropathic symptoms such as thermal hypoalgesia. Likewise, degeneration of A␤ fibers leads to a loss of vibration and tactile sensation (Lennertz et al, 2011) with axon-myelin separation (Powell and Myers, 1983;Myers and Powell, 1984;Love et al, 1986) and eventual segmental demyelination in long-term DPN (Zochodne, 2007). Thus, deficits in both C and A␤ fiber function greatly affects the detection of noxious and non-noxious stimuli.…”
Section: Dpnmentioning
confidence: 99%